The Role of antibody in immunity to Pseudomonas pseudomomallei in mice - Jeanne Indriana; Robert G. Hirst (Hemera Zoa, 1992)
Passively transfered rabbit antiserum provided some protection to Balb/c mice against challanged with viable virulent goat (XI003) strain of Pseudomonas pseudomallei. This protection was demonstrated in mice injected with 1:10 and 1:20 dilutions of antiserum. A. complete protection was conferred to the mice injected with 1:20 dillution and wich then were challanged with log10 3,5 and log10 4,5 viable cells of homologous strain. In contrast, the undiluted antiserum (neat) did not give any protection in mice. Nevertheless, these findings showed that antibody plays a role in immunity to P. pseudomallei